WOMEN AS A STRATEGIC GROUP: WOMEN'S STRATEGY IN POLITICAL NETWORKS THROUGH THE ECONOMIC AREA: (IWAPI NTB CASE STUDY) - Safitri, Purnami; Trisno Aji, Wahyu; Adabiyah, Radiyatun; Harani, Faizah (Politea : Jurnal Politik Islam, 2024)
Abstract Women’s participation in economic field and politic is often viewed in a dichotomous manner, where the economy is referred as "low politics." Women’s participation in economic organization is also seen as non-strategiv activism, which interpreted as activities that are distant or excluded from electoral politics and has less influence on the decision-making process. This research aims to challenge the argument and suggests that women's roles in the economy are indeed interconnected with the political sector. The study argues that women use their institutional capital as members of IWAPI to build relationships and political networks, where the appropriation of interests which means securing access to specific resources is the main goal. This research utilizes the Strategic Group theory from Evans Dieter-Evers and finds that women affiliated with IWAPI adopt personal and corporate appropriation modes in pursuing their interests. Personal appropriation is closely related to strengthening political networks through political parties to drive institutional change, while corporate appropriation is carried out by IWAPI members through expanding business networks and forming resource alliances. Furthermore, women can be categorized as a strategic group with business types and often employ cooperative strategies with other strategic groups. IWAPI is ultimately referred to as an organization formed by strategic groups of women for the appropriation of specific interests. Keywords: Women, strategic groups, agency, appropriation of interests